2023
DOI: 10.3390/ijms24054641
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of MYB Transcription Factors and Screening of MYBs Involved in the Red Color Formation in Rhododendron delavayi

Abstract: Flower color is one of the crucial traits of ornamental plants. Rhododendron delavayi Franch. is a famous ornamental plant species distributed in the mountain areas of Southwest China. This plant has red inflorescence and young branchlets. However, the molecular basis of the color formation of R. delavayi is unclear. In this study, 184 MYB genes were identified based on the released genome of R. delavayi. These genes included 78 1R-MYB, 101 R2R3-MYB, 4 3R-MYB, and 1 4R-MYB. The MYBs were divided into 35 subgro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 70 publications
0
0
0
Order By: Relevance
“…From an evolutionary point of view, studies have shown that 2R-MYB transcription factors are distributed in fungi, animals, and plants, indicating that 2R-MYB transcription factors are relatively ancient and conserved [60]. The abundance of 2R-MYB genes is predominant in both A. thaliana and spinach, and this discovery has also been found in Rhododendron delavayi [61], mainly because the 2R-MYB transcription factor is amplified in higher plants, increasing the number of 2R-MYB genes. In combination with an evolutionary perspective, a relatively conservative structure that has a relatively conserved function may be related to the stability of the plant's genetic material and its ability to adapt to the environment with more favorable traits [62].…”
Section: Discussionmentioning
confidence: 92%
“…From an evolutionary point of view, studies have shown that 2R-MYB transcription factors are distributed in fungi, animals, and plants, indicating that 2R-MYB transcription factors are relatively ancient and conserved [60]. The abundance of 2R-MYB genes is predominant in both A. thaliana and spinach, and this discovery has also been found in Rhododendron delavayi [61], mainly because the 2R-MYB transcription factor is amplified in higher plants, increasing the number of 2R-MYB genes. In combination with an evolutionary perspective, a relatively conservative structure that has a relatively conserved function may be related to the stability of the plant's genetic material and its ability to adapt to the environment with more favorable traits [62].…”
Section: Discussionmentioning
confidence: 92%
“…Apart from structural genes, anthocyanin biosynthesis is also regulated by several TFs, in which MYB, bHLH, and WD repeats form the MBW ternary complex to regulate transcription levels of the structural genes that participate in the anthocyanin and proanthocyanidin biosynthesis pathways [56]. MYB plays a critical role in MBW complexes for its tissue-specific expression and binding to specific DNA sequences [57]. Some studies have shown that MYB can enhance or inhibit anthocyanin biosynthesis.…”
Section: Tfs Related To Anthocyanin Biosynthesismentioning
confidence: 99%